2019
DOI: 10.3390/su11113174
|View full text |Cite
|
Sign up to set email alerts
|

Walk More towards Active Leisure, Tourism, Culture, and Education

Abstract: Background: This article addresses the following question: why don’t primary and secondary school students perform urban walks or hikes during cultural and tourist visits of the cities they live in, when engaging in physical activity (PA)? The aim is to demonstrate that exploring cities on foot is a different, important, and necessary way to perform PA, that leads to improving social relations and exposing individuals to culture; in particular, teachers would be trained for this. Methods: qualitative methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Furthermore, they showed that 7% of the participants in their study changed their behavior in terms of daily mobility when they returned home, and most of them walked or cycled more often. In this context, we considered the work of Cachón-Zagalaz et al [50] for an important new approach to PA among young people, in realizing the benefits of combining urban walking with exploring cities.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they showed that 7% of the participants in their study changed their behavior in terms of daily mobility when they returned home, and most of them walked or cycled more often. In this context, we considered the work of Cachón-Zagalaz et al [50] for an important new approach to PA among young people, in realizing the benefits of combining urban walking with exploring cities.…”
Section: Discussionmentioning
confidence: 99%
“…The ethnic traditional sports culture summarizes the experience of the forefathers living in this land, the Chinese land, the daily labor life, and the crystallization of wisdom, which is the product of historical development [9][10]. Ethnic traditional sports are not only an important form of sports culture but also fully embody the common values of human beings in sports, which are a special kind of physical culture [11][12][13].…”
Section: Introductionmentioning
confidence: 99%